Cognitive reserve moderates long-term cognitive and functional outcome in cerebral small vessel disease. Issue 12 (7th October 2016) - Jokinen, Hanna; Melkas, Susanna; Madureira, Sofia; Verdelho, Ana; Ferro, José M; Fazekas, Franz; Schmidt, Reinhold; Scheltens, Philip; Barkhof, Frederik; Wardlaw, Joanna M; Inzitari, Domenico; Pantoni, Leonardo; et al.
Abstract : Background: Cerebral small vessel disease (SVD) is characterised by progressive white matter hyperintensities (WMH), cognitive decline and loss of functional independence. The correspondence between neuroimaging findings and the severity of clinical symptoms has been modest, however, and thus the outcome may be affected by various host factors. We investigated the predictive value of educational and occupational attainments as proxy measures of cognitive reserve on long-term cognitive and functional outcome in patients with different degrees of WMH. Methods: In the Leukoaraiosis and Disability (LADIS) study, 615 older individuals with WMH were evaluated with brain MRI and detailed clinical and neuropsychological assessments at 3-year follow-up. A prolonged follow-up of functional and cognitive status was administered with a structured telephone interview after up to 7 years. Results: Higher levels of educational and occupational attainment were strongly related to baseline cognitive scores and predicted a slower rate of decline at 3-year follow-up in measures of processing speed, executive functions and memory independently of WMH volume and other confounders. The deleterious effect of WMH on processing speed and memory was moderated by education and occupation. Education mitigated the relation of WMH volume on 7-year cognitive status. Moreover, higher education and occupational attainments were related to favourable outcome at 7-year follow-up as defined by sustained functional independence and lower mortality. Conclusions: The results support the presumption that cognitive reserve plays a significant role as a buffer against the clinical manifestations of SVD and may in part explain high individual variability in outcome.